Laterally Transported Particles From Margins Serve as a Major Carbon and Energy Source for Dark Ocean Ecosystems. Issue 18 (16th September 2020) - Shen, Jiaming; Jiao, Nianzhi; Dai, Minhan; Wang, Haili; Qiu, Guoqiang; Chen, Jianfang; Li, Hongliang; Kao, Shuh‐Ji; Yang, Jin‐Yu Terence; Cai, Pinghe; Zhou, Kuanbo; Yang, Weifeng; et al.
Abstract: Deep ocean microorganisms consume particulate organic matter that is produced in the surface ocean and exported to deeper depths. Such consumption not only enriches inorganic carbon in the deep ocean but also transforms organic carbon into recalcitrant forms, creating an alternative type of carbon sequestration. However, estimates of deep microbial carbon demand substantially exceed the available particulate organic carbon exported from the euphotic zone, resulting in an unbalanced dark ocean carbon budget. Here, we combined field‐based microbial activity parameters, integrated multiyear particle export flux data, sinking particle fluxes measured by sediment traps, and optical data from Biogeochemical‐Argo floats to quantify the main sources of organic carbon to the dark ocean. Laterally transported particles (including sinking and suspended particles) serve as a major energy source, which directly provide organic carbon and enhance new organic carbon production by dark carbon fixation, reconciling the mismatch in the regional carbon budget. Plain Language Summary: Particulate organic matter, produced by phytoplankton in the upper ocean, can sink through the water column and act as a source of organic matter to the deep ocean. These particles are decomposed to carbon dioxide by microorganisms, resulting in dissolved inorganic carbon and organic carbon resistant to decomposition in the deeper ocean. This process controls the biological sequestration of CO2 by the oceans. However, there is an imbalance between the low amount of organic carbon exported from the photic zone and the high microbial demand for carbon in the dark ocean. We attempted to explain how the deep ocean carbon and energy supply can meet the microbial metabolic demand. Four main organic carbon sources were measured and quantified in the South China Sea: particles that come from the photic zone, particles that move laterally through the ocean, dark carbon fixation, and dissolved organic carbon. We found that laterally transported particles from the surrounding margins provide a direct source of organic carbon and also allow for much new organic carbon production through dark carbon fixation. These particles, which provide a major energy source to dark ocean ecosystems, help resolve the mismatch in the regional carbon budget. Key Points: Data from Biogeochemical‐Argo floats showed direct evidence of episodic pulses of laterally transported particles into the deep sea Laterally transported particles are a direct organic carbon source and also enhance new organic carbon production by dark carbon fixation Laterally transported particles provide major carbon and energy for deep ecosystems, reconciling the mismatch in the regional carbon budget